MAKROZOOBENTHOS PANTAI PERERENAN (KABUPATEN BADUNG): JENIS, STATUS, DAN MANFAATNYA BAGI MASYARAKAT - Intan Wiratmini, Ngurah; Wiryatno, Joko; Raka Dalem, A.A.G. (Bumi Lestari; Vol 8 No 2 (2008))
The research was undertaken on Pererenan beach in the Regency of Badung, Bali Province, between September and December, 2006. The study sites occur close to the downstream of Bausan creek, the location of which were part of ”Subak Kedungu” irrigation system (east of the creek) and ”Subak Munggu Tegal Lantang” irrigation system (west of the creek). Samples were taken on low tides periods of the intertidal zones of the beach. Samples were stratified randomly taken on three kinds of substrates: on sand and coral substrates on the west, sand substrates in the middle and hard sandstone on the east, each of which consist of five quadrates of 40 cm x 40 cm. Results of this research showed that on the site have been successfully identified 17 species of macrozoobenthic fauna. None of them were classified as protected species. The macrozoobenthic fauna on Parerenan beach had a medium level of index of diversity (IK = 2,598). This meant that, the beach ecosystem in Pererenan was in a stable condition with a medium level of diversity. From the benefit and problems related to their occurrence, it can be described that macrozoobenthic organisms on this study sites, some can be consumed. Besides, there were also some species which dangerous to human because they can cause bleeding, or dangerous hurt caused by sharp needles.
Keywords: macrozoobenthic organisms, Pererenan beach, intertidal, diversity, ecosystem